Continual monitoring of intraepithelial lymphocyte immunophenotype and clonality is more important than snapshot analysis in the surveillance of refractory coeliac disease. Issue 4 (8th December 2009) - Liu, H; Brais, R; Lavergne-Slove, A; Jeng, Q; Payne, K; Ye, H; Liu, Z; Carreras, J; Huang, Y; Bacon, C M; Hamoudi, R A; Save, V; et al.
Abstract : Objective: An aberrant immunophenotype and monoclonality of intraepithelial lymphocytes (IELs) are frequently found in refractory coeliac disease (RCD). However, the utility of continual monitoring of IEL immunophenotype and clonality in the surveillance of RCD remains to be studied. Design: The diagnostic and follow-up biopsies from 33 patients with CD, 7 with suspected RCD, 41 with RCD and 20 with enteropathy-associated T cell lymphoma (EATL) (including 11 evolved from RCD) were investigated by CD3ɛ/CD8 double immunohistochemistry and PCR-based clonality analysis of the rearranged T cell receptor (TCR) genes. Results: An aberrant immunophenotype (CD3ɛ + CD8 − IELs ≥40%) and monoclonality were detected occasionally in CD biopsies, either transiently in patients with CD not compliant with a gluten-free diet or in those who subsequently developed suspected RCD, RCD or EATL. In contrast, the aberrant immunophenotype and monoclonality were found in 30 of 41 (73%) and 24 of 37 (65%) biopsies, respectively, at the time of RCD diagnosis. Among the patients with RCD who did not show these abnormalities in their diagnostic biopsies, 8 of 10 (80%) and 5 of 11 (45%) cases gained an aberrant immunophenotype and monoclonality, respectively, during follow-up. Irrespective of whether detected in diagnostic or follow-up biopsies, persistence of both abnormalities was characteristic of RCD. Importantly, the presence of concurrent persistent monoclonality and aberrant immunophenotype, especially ≥80% CD3ɛ + CD8 − IELs, was a strong predictor of EATL development in patients with RCD (p=0.001). Conclusions: Continual monitoring of both immunophenotype and clonality of IELs is more important than snapshot analysis for RCD diagnosis and follow-up, and could provide a useful tool for surveillance of patients at risk of EATL.